Actividad tripanocida de asteráceas nativas del Norte Argentino - Elso, Orlando G.; Nápoles Rodríguez, R.; Viecenz, J.M.; Bach, Hernán Gerónimo; Bontempi, E.; Sulsen, Valeria P. (Facultad de Farmacia y Bioquímica, Universidad de Buenos Aires, 2022)
Poster